The Effectiveness of Collaborative and Discovery Learning Methods in Improving Students’ Creative Thinking Ability in “Aqidah Akhlaq” Learning in Madrasah Tsanawiyah - Lilis Nurul Wahidah; Rihab Wit Daryono (IJORER : International Journal of Recent Educational Research, 2024)
Objective: The researcher chose a topic of discussion regarding the comparison of 2 learning models that are theoretically effective for use in the classroom when learning Aqidah Akhlak. In its application, learning the Aqidah Morals can be delivered through several methods. This research aims to test the effectiveness of collaborative and discovery learning models on students' creative thinking skills. Method: The research method used was a pre-test and post-test design experiment. The research sample consisted of 2 classes divided into two groups, namely two experimental groups that used collaborative and discovery learning models. The data analysis technique used in this research is the normality test using the Shapiro-Wilk, independent sample t-test, paired sample t-test, and N-Gain tests. Results: After the treatment, the data analysis from the post-test scores can be seen. Based on the N-Gain Test shows that creative thinking skills increased significantly in both groups after treatment, with data results in the collaborative group being 0.46 < 0.70 in the medium category and the discovery group only 0.27 < 0.30 in the low category. These data showed a more significant improvement in the group that received collaborative learning than in the discovery group. Novelty: This research presents novelty, which lies in the comparative approach taken to analyze the two methods simultaneously, as well as the use of holistic, quantitative measuring tools to identify significant changes in students' creative thinking abilities.